METHODS OF THE APPROXIMATE ESTIMATIONS OF FATIGUE DURABILITY OF COMPOSITE AIRFRAME COMPONENT TYPICAL ELEMENTS - V. E. Strizhius (Научный вестник МГТУ ГА, 2016)
Methods of the approximate estimations of fatigue durability of composite airframe component typical elements which can be recommended for application at the stage of outline designing of the airplane are generated and presented.